A nurse-led coaching intervention with home telemonitoring for patients with heart failure: Protocol for a feasibility randomized clinical trial - Ines Basso; Erika Bassi; Silvia Caristia; Angela Durante; Cristian Vairo; Salvatore Giuseppe Rocco Patti; Mario Pirisi; Mauro Campanini; Marco Invernizzi; Mattia Bellan; Alberto Dal Molin; Francesca Caldera; et al. (MethodsX, 2024)
Poor treatment adherence and lack of self-care behaviors are significant contributors to hospital readmissions of people with heart failure (HF). A transitional program with non-invasive telemonitoring may help sustain patients and their caregivers to timely recognize signs and symptoms of exacerbation.We will conduct a Randomized Clinical Trial (RCT) to evaluate the feasibility and acceptability of a 6-month supportive intervention for patients discharged home after cardiac decompensation. Forty-five people aged 65 years and over will be randomized to either receive a supportive intervention in addition to standard care, which combines nurse-led telephone coaching and a home-based self-monitoring vital signs program, or standard care alone. Four aspects of the feasibility will be assessed using a mixed-methods approach: process outcomes (e.g., recruitment rate), resources required (e.g., adherence to the intervention), management data (e.g., completeness of data collection), and scientific value (e.g. 90- and 180-day all-cause and HF-related readmissions, self-care capacity, quality of life, psychological well-being, mortality, etc.). Participants will be interviewed to explore preferences and satisfaction with the intervention. The study is expected to provide valuable insight into the design of a definitive RCT.